Seismic vulnerability analysis of various types of dams with finite element methods - Farsangi, Ehsan Noroozinejad (2010)
In recent years, the seismic verification of structures has dramatically evolved. Malaysia is surrounded by countries such as Indonesia and Philippine that has experienced many great earthquakes; hence it would be unwise to totally ignore the effects of earthquakes on structures in Malaysia. The purpose of this study is to investigate the vulnerability of existing Dams in Malaysia region under earthquake ground motion because In case of severe ground motions, substantial cracking is likely to develop across significant regions of the dam, and its consequences must be taken into account for a rigorous seismic evaluation. By evaluating the seismic performance of the dams we can predict dam’s resistance to prevent economic damage and loss of human life in case of dam failure. In this study we present the results of the case studies of the earthquake response on various types of dams (Concrete, Rockfill and Earthfill Dams). To achieve this purpose, dams have been remodeled using SAP2000 and PLAXIS. Three different analysis methods (Free Vibration, Time History and Response Spectrum) have been implemented in this Project to study the behavior of these dams under earthquake loading, Seismic hazard was represented by the peak ground acceleration at the dam site. After analyzing the dams in SAP2000 and PLAXIS we will compare the existing stress from the output data with dams’ capacity to identify the critical parts of the dams under earthquake loading. This problem can be efficiently tackled with necessary boundary conditions with finite element technique. The dams considered in the present investigation, are analyzed by two dimensional plane strain formulations with four node quadrilateral elements in SAP2000 and 15-noded triangular elements in PLAXIS. We have done the response spectrum and linear time history analysis by using SAP2000 and Non-linear dynamic analysis by means of PLAXIS. Both softwares have included soil-structure interaction in analysis.